2018
DOI: 10.3389/fbioe.2018.00149
|View full text |Cite
|
Sign up to set email alerts
|

A Cortical Thickness Mapping Method for the Coxal Bone Using Morphing

Abstract: As human body finite element models become more integrated with the design of safety countermeasures and regulations, novel models need to be developed that reflect the variation in the population's anthropometry. However, these new models may be missing information which will need to be translated from existing models. During the development of a 5th percentile female occupant model (F05), cortical thickness information of the coxal bone was unavailable due to resolution limits in the computed tomography (CT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The acetabular cortical bone thickness measurement is presented in four cross-sections. The measured thicknesses were consistent with Giudice et al [40], who reported the ranges of 0-2.4 mm and 1.8-3.6 mm for the cortical thicknesses of the acetabular fossa and rim of the acetabulum, respectively. Table A4.…”
Section: Data Availability Statementsupporting
confidence: 90%
See 2 more Smart Citations
“…The acetabular cortical bone thickness measurement is presented in four cross-sections. The measured thicknesses were consistent with Giudice et al [40], who reported the ranges of 0-2.4 mm and 1.8-3.6 mm for the cortical thicknesses of the acetabular fossa and rim of the acetabulum, respectively. Table A4.…”
Section: Data Availability Statementsupporting
confidence: 90%
“…The location-dependent cortical thickness was obtained via a semi-automated slice-by-slice local thresholding procedure available in Mimics ® . The cortical thicknesses obtained, especially at the acetabulum (the thinnest cortical bone within the pelvis), were checked to make sure that they were in the typical reported range for the pelvic cortical bone [39,40] (Appendix A, Figure A1). Since an abdominal CT image was used in this study, only the proximal part of the femur was reconstructed directly.…”
Section: Three-dimensional (3d) Model Preparationmentioning
confidence: 99%
See 1 more Smart Citation